(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Communication is of the utmost importance in management, since understanding employees issues, social relationship sustainability, managers capacity of motivating and leading subordinates and the relationships with the external environment in which the company operates, rely heavily on the quality of communication. Basically the communication issue is in management the issue of circulating ideas and solutions oriented towards achieving the companys objectives through open channels of communication both inside and outside the company. The paper shows that the managers contribution goes beyond the economic side, equally important being the social efficiency revealed by aspects that cannot be quantified directly but with multiple consequences upon all factors involved in a companys activities and especially upon the human factor.